A Model of Photovoltaic Module of Solar Station (Eurasian Journal of Learning and Academic Teaching, 2023)
This paper define a circuit-based simulation model for a PV cell in order to allow estimate the electrical behavior of the cell with respect changes on environmental parameter of temperature and irradiance. An accurate PV module electrical model is presented based on the mathematical equations. The general model was implemented on MATLAB/Simulink environment, and accepts irradiance as variable parameters and outputs the I-V characteristic